MENGURAI PERMASALAHAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Amin, Rizal Irvan; Achmad, Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
The acute problem of regulation, both in terms of quantity and quality, is a inevitability. There has been discrepancy in the formation of laws and regulations, namely the mismatch between expectations and reality. This research aims to present and explain a portrait of the laws and regulations in Indonesia, both in terms of quantity and quality. This research is a prescriptive normative legal research through literature study use technical data analysis related to the themes discussed. Result research shows that there is an acute problem in the laws and regulations in Indonesia, where in quantity and obesity quality experiences conflict, overlap, inconsistency, multiple interpretations, and not operational. Lack of understanding of the nature of regulation and insecurity in maintaining the quality of the national legal system results in inability legal system to realize state finances. Therefore, it is needed an extraordinary breakthrough through a regulatory reform in order to regulate quantity laws and regulations can be controlled proportionally and the quality of the regulations legislation can also be improved.